Level Knowledge of Farmers on The Implementation of Balanced Fertilizer; Ratio of Fertilizer to Land Area for Increasing Production - Herdiana Herdiana; Yudi Hermawan (Jurnal Penelitian Pendidikan IPA, 2023)
The nature of farmers' dependence on chemical fertilizers or inorganic fertilizers makes farmers even more helpless when subsidized fertilizers are scarce. The agricultural system in Central Lombok is mostly rainfed, because this area is classified as a tropical area. The research location is in Masjuring Village, West Sub-District, Central Lombok Regency, West Nusa Tenggara which will be carried out for 8 months, namely from November 2022-June 2023, the data comes from primary and secondary data. The research results were analyzed using SPSS Version 21 analysis which showed that the majority of farmers were very supportive of research activities because they received great benefits in carrying out farming activities. Prior to the implementation of the research activities, the majority of farmers had low knowledge of balanced fertilizers, both the concept, purpose and benefits of applying balanced fertilizers which were in ranges 2 and 3, namely they did not know and did not know and after the activity there was an increase in knowledge related to the effectiveness of program implementation. will be applied. Based on the results of the Spearman rank test using SPSS, it is known that the significance value or sig (2-tailed) is 0.0380 because the sig (2-tailed) value is 0.0380 < smaller than 0.005, which means that there is a significant relationship between the knowledge level of farmers and the effectiveness of fertilizer application. balanced. The higher the farmer's knowledge of various aspects related to the program, the higher the farmer's awareness of the benefits of the program